What Are The Effects of Silibinin on Testicular Tissue of Mice? - Hayder G. Oufi, Nada N. Al-Shawi and Saad AR. Hussain (Journal of Applied Pharmaceutical Science)
Silibinin (silybin) is one of the structural isomers of the flavonoid silymarin, and it has wide variety of phytotherapeutic applications and the aim of this study was to investigate the effects of different doses of silibinin on testicular tissue of mice. Twenty male Swiss albino mice were divided into four groups. Each group consist of five animal, (Group 1) (negative control) animals were administered single intraperitoneal (IP) daily dose of phosphate buffer for 5 days, Groups ( 2, 3, and 4) were given a single IP daily dose of either (50, 100 or 150 mg/kg B.wt.) of silibinin respectively for 5 days. Microscopic examinations of sperms, histological examinations of testes and serum testosterone level had been measured. It was found that silibinin in doses of (100 or 150) mg/Kg produced a significant increase (P
Keywords: Silibinin,Silymarin,Testosterone,Leydig cell,Testicular tissue.